KONSEP RIDA DALAM AL-QUR'AN DAN HADIS SERTA PENERAPANNYA DALAM BIMBINGAN ROHANI PASIEN RUMAH SAKIT ISLAM DI JAWA BARAT (Telaah Deskriptif Analitik di RS Muhammadiyah Kota Bandung dan RS Al-Ihsan Kabupaten Bandung) - Irwan Abdurrohman; Ecep Ismail; Dewi Mariyana (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
Besides relying on medical equipment and chemical drugs, at this time the care of patients in the hospital began to use a spiritual care approach. This is do as to increase the motivation for healing and a sense of acceptance the disease that is being suffered. The research was conducted with the aim to explain the meaning of rido from several professional spiritual advisors and explain the strategies used by spiritual advisors to build rido attitude to their patients. The approach in this study is qualitative and the method used is descriptive, by analyzing the social, psychological and phenomena that occur in the field. The results of this study are: (1) According to binroh, rido is the attitude of accepting a patient, for an examination in the form of an illness which he suffers with patience and perseverance, always endeavors to take medication and try to get closer to Allah swt. by worshiping and surrendering his healing to Allah swt. Rido is very closely related to ignorance. To reach the level of rido, a servant must believe and be pious. Thus, the patient is guided first to uphold the pillars of faith, then guided to worship. If faith and piety have grown, rido will be achieved in every situation. (2) The binroh strategy of RSUD Al-Ihsan in growing the patients rido attitude is that the binroh gives an example to the patient how to accept with a sincere heart. Furthermore, the binroh guides patients to carry out programs that can later foster a rido attitude. Both the daily, monthly and even annual programs that have been created by binroh. The binroh strategy of RS Muhamadiyah Hospital is to meet face to face, conduct counseling, tell the problem being faced. The binroh also teaches the obligatory worship services, pray and surrender to Allah swt. and providing therapies in the form of relaxation, motivating and telling the story of the prophet for patients who are still children.